2018
DOI: 10.1093/mnras/sty2684
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for conservative mass transfer in the classical Algol system δ Librae from its surface carbon-to-nitrogen abundance ratio

Abstract: Algol-type binary systems are the product of rapid mass transfer between the initially more massive component to its companion. It is still unknown whether the process is conservative, or whether substantial mass is lost from the system. The history of a system prior to mass exchange is imprinted in the photospheric chemical composition, in particular in the carbon-to-nitrogen (C/N) ratio. We use this to trace the efficiency of mass-transfer processes in the components of a classical Algol-type system, δ Libra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…In that case, the surface carbon abundance of the gainer cannot be lower than that of the donor star, however. Multiple authors have used the sketched scenario to explain the surface abundance anomalies observed in several other Algol-type stars; these include Ibanoǧlu et al (2012) for GT Cep, AU Mon, and TU Mon, Kolbas et al (2014) for u Her, and Dervişoglu et al (2018) for δ Lib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, the surface carbon abundance of the gainer cannot be lower than that of the donor star, however. Multiple authors have used the sketched scenario to explain the surface abundance anomalies observed in several other Algol-type stars; these include Ibanoǧlu et al (2012) for GT Cep, AU Mon, and TU Mon, Kolbas et al (2014) for u Her, and Dervişoglu et al (2018) for δ Lib.…”
Section: Discussionmentioning
confidence: 99%
“…Tkachenko et al (2008Tkachenko et al ( , 2009 confirmed the finding of the two spots, resuming the interpretation. Dervişoglu et al (2018) and Berdyugin et al (2018), on the other hand, give an alternative explanation, showing for the short-period Algols δ Lib and λ Tau that the mass stream can produce a light scattering cloud in front of the surface of the Roche lobe filling secondary facing the primary.…”
Section: Analysis With Phoebementioning
confidence: 99%
“…In semi-detached and contact binaries one or both components fills their Roche lobe and mass can be transferred between them or lost from the system. These objects are laboratories for tidal effects, case A mass transfer (during the main sequence), case B mass transfer (during evolution to the giant phase), mass loss, and orbital angular momentum loss (e.g., [27]). When mass is stripped from the originally more massive star it reveals the deep interior and gives a window onto thermonuclear fusion in stars [28][29][30].…”
Section: Importance Of Binary Starsmentioning
confidence: 99%
“…Evolved binaries. Mass transfer in semi-detached and contact binaries remains poorly understood [27,352] and can lead to stellar mergers [353]. The common-envelope phase of binary evolution is also difficult [354,355], and once a binary has got past these obstacles it exhibits many complex phenomena [356].…”
Section: Future Workmentioning
confidence: 99%
“…To explore the parameter space, as well as to obtain error estimates, many researchers utilize Markov-Chain Monte-Carlo (MCMC; Goodman & Weare 2010) based optimisers (e.g. Lehmann et al 2020, Dervişoǧlu et al 2018. For the purpose of optimising the aforementioned nine free parameters, we developed a Python framework (LC MCMC ) which uses PyWD2015 To obtain a good fit, we sampled parameter priors with a normal distribution around 10 % sigma.…”
Section: Parametermentioning
confidence: 99%